FISSION TRACK DATING OF PHOSPHATE MINERALS AND THE THERMOCHRONOLOGY OF APATITE - Gleadow A.J.W.; Belton D.X.; Kohn B.P.; Brown R.W. (My University, 2002)
Several phosphate minerals have been investigated for their usefulness in geochronology and thermochronology by the fission track method. Of these, apatite Ca5(PO4)3(F,Cl,OH)], has proved pre-eminently suitable for this purpose for reasons discussed below. Apatite was one of the first minerals, amongst many others, to be investigated for fission track dating by Fleischer and Price (1964) and has subsequently become by far the most important of all the minerals used for dating by this method. The usefulness of apatites for fission track dating arises from their near-universal tendency to concentrate uranium within their structure at the time of crystallization and their widespread occurrence in all of the major rock groups.